Intraoperative Nociception Monitoring by qNOX Score Using Three Different Doses of Fentanyl - Alisha Kaur; Nandita Mehta; Sunana Gupta (Dr. Annil Mahajan, 2021)
Background: The qCON and qNOX scores in the conox monitor measures depth of anaesthesia and analgesia respectively. qNOX, a parameter extracted from the raw EEG could predict the likelihood of movement response to different anaesthetic and surgical stimuli.  Various workers have used various doses of fentanyl to find an optimal dose that will achieve adequate analgesia and at the same time will reduce the occurrence of its side effects. Purpose: Primary objective was to study and compare the effect of three different doses of fentanyl on nociception score qNOX and secondary objective was to compare the number of doses of Inj paracetamol used and extubation time in three groups. Material and Methods: Study was done in ninety patients scheduled for elective surgery under general anaesthesia who were randomly assigned to group I, II and III to receive fentanyl in the dose of 1, 1.5 and 2 microgram/kg respectively.  Parameters recorded were values of qNOX scores at various time intervals, number of patients requiring Inj paracetamol intraoperatively, extubation time and any side effect of study drug in all the three groups. Results: The mean values of qNOX score and Inj paracetamol required intraoperatively was highest in the group of patients who received fentanyl in the dose of 1 mcg/kg and lowest in patients who received fentanyl in the dose of 2 mcg/kg. The difference between all the three groups was statistically significant (p<0.05). The mean extubation time was insignificant between group 1 and II, Group II and III but was significant between I and III (p<0.05). Conclusion:  Fentanyl in a dose of 2 micrograms per kg was able the achieve desired qNOX scores intraoperatively without any serious side effects.